Local Government Policies in Analysis Of Community and Creating Health of A Fisherman Village in Pahlawan Village, Tanjung Tiram in Batu Bara District - Hapsah Maysaroh; Bachtiar Efendi; Rusiadi (International Journal of Economic, Technology and Social Sciences (Injects), 2022)
This study entitled the analysis of community participation, local government policy in creating the health of fishing villages in Pahlawan Village, Tanjung Tiram District, Batu Bara District. The purpose of this study was to determine (1) the effect of household involvement and community care in creating health in the Fisherman Village (2) The effect of the form of community activities in creating the health of the Fisherman Village. (3) Effect of paragraph 5 regarding requirements for controlling environmental impacts in creating health in Fishermen's Villages. (4) The influence of regional regulation number 36 of 2009 concerning the arrangement of rural areas in creating the health of Fishermen's Villages. (5) Influence of household involvement, and community care, form of community activities, Paragraph 5 on environmental impact control requirements and Regional Regulation number 36 of 2009 concerning structuring of rural areas in creating health in Fishermen's Villages. The results of this study indicate that: (1) the variables of household involvement and community concern have a partial effect of 0,000. (2) the variable form of community activities partially influences 0.029. (3) variable paragraph 5 regarding the requirements for controlling environmental impacts partially influences by 0,000. (4) Regional regulation variable number 36 of 2009 concerning structuring of rural areas has no partial effect of 0.636. (5) The variable of household involvement and community concern, the form of community activities, paragraph 5 of the environmental impact control requirements and regional regulation number 36 of 2009 concerning the arrangement of rural areas simultaneously influences health by 0,000.